2004
DOI: 10.1530/eje.0.1500841
|View full text |Cite
|
Sign up to set email alerts
|

Selenium has a protective role in caspase-3-dependent apoptosis induced by H2O2 in primary cultured pig thyrocytes

Abstract: Objective: Hydrogen peroxide (H 2 O 2 ), necessary for thyroid hormonogenesis, is produced at the apical surface of the thyroid follicular epithelium. Excess H 2 O 2 is potentially cytotoxic and may contribute to the development of hypothyroidism, e.g. in severe selenium deficiency. Yet it is unclear how H 2 O 2 contributes to thyroid cell death. Design and methods: H 2 O 2 -induced apoptosis and necrosis were studied in primary cultured pig thyroid cells. Glutathione peroxidase (GPx) activity was altered by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 36 publications
(33 reference statements)
2
32
0
8
Order By: Relevance
“…The studies showed a stronger preventive action of selenium on the morphological picture of the thyroid. 42,43 Administration of selenium nanoparticles to rats inhibited the development of changes observed in thyroids after exposure to K 2 Cr 2 O 7 . The present result is the first report on cellular thyroid toxicity induced by Cr(VI) and amelioration of this damage by administration of nano-selenium.…”
mentioning
confidence: 99%
“…The studies showed a stronger preventive action of selenium on the morphological picture of the thyroid. 42,43 Administration of selenium nanoparticles to rats inhibited the development of changes observed in thyroids after exposure to K 2 Cr 2 O 7 . The present result is the first report on cellular thyroid toxicity induced by Cr(VI) and amelioration of this damage by administration of nano-selenium.…”
mentioning
confidence: 99%
“…У подальшому настає заміщення пошкоджених клі-тин сполучною тканиною з розвитком первинного гіпотиреозу. Доведено, що селен не тільки посилює продукцію GPx, зменшуючи прояви оксидативно-го стресу та справляючи імуномодулюючий вплив, а й пригнічує транскрипційний фактор NF-B, що призводить до гальмування експресії прозапаль-них цитокінів, а також справляє дозозалежний інгі-буючий вплив на експресію молекул HLA-DR тире-оцитів, індуковану інтерфероном гамма, що вказує на перспективність використання сполук селену в лікуванні АІТ [9,10,13].…”
Section: том 13 № 1 2017unclassified
“…Про-довження термінів прийому препаратів до шести місяців супроводжувалося подальшим зменшенням концентрації АТ-ТПО, що, на думку авторів, від-бувалося за рахунок збільшення внутрішньотирео-їдного вмісту селену й активності GPx [32]. Окрім зазначених механізмів, інші науковці позитивний вплив сполук селену при АІТ пов'язують із зрос-танням активності TR в тканині ЩЗ [13], а також з імунотропною дією, що забезпечується здатністю цього мікроелемента активувати гени, які кодують прозапальні цитокіни [10,25]. У більшості з проведених подальших досліджень селен призначали у формі селенометіоніну або селе-ніту натрію (50-200 мкг на добу) протягом 3-12 мі-сяців.…”
Section: том 13 № 1 2017unclassified
See 1 more Smart Citation
“…A unique reaction of the C5ʹ-centered sugar radical is addition to the C8-position of the purine ring of the same nucleoside. This reaction leads to intramolecular cyclization, followed by 8,5-cyclopurine-2ʹ-deoxynucleosides after oxidation [41,42]. Both 5ʹR-and 5ʹS-diastereomeres of 8,5ʹ-cyclo-2ʹ-deoxyguanosine (cyclo-dG) and 8,5ʹ-cyclo-2ʹ-deoxyadenosine (cyclo-dA) are formed in DNA [41,42].…”
Section: Oxidation Of Saccharidesmentioning
confidence: 99%